Produktivitas Kerja Satpam di Universitas Islam Negeri Sumatera Utara Tuntungan - Faris N, Tengku Muhammad; Ananda Br.SK, Dea; Maishie Salwa, Jihan; Asiyah Siregar, Nur; Aulia, Rizka; Araafi, Alif; Aidha, Zuhrina (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
Security and safety are crucial aspects in various situations, including in the academic environment. This research aims to examine the factors that influence the work productivity of security units (security guards) at the North Sumatra State Islamic University (UINSU) Tuntungan. The research was conducted using a qualitative phenomenological approach, involving interviews with security guards as respondents. Work productivity is measured based on the level of attendance and implementation of tasks during the period March to May 2024. The research results show that the productivity of security guards has decreased during this period, with productivity values ​​of 98.92% in March, 97.7% in April, and 95.69 % in May 2024. This decrease in productivity was caused by increased workload due to employee absenteeism. The higher the attendance level, the higher the security guard's work productivity, and vice versa. Therefore, controlling attendance and applying discipline through a reward and punishment system is proposed as a strategy to increase the work productivity of security guards at UINSU Tuntungan.